The role of the family in reducing University violence from the viewpoint of a Jordanian Government University students - Momani, Taghreed; Al Abed, Rowaydah (Dirasat: Educational Sciences, 2020)
The study aimed to define the role of the family in reducing university violence from the point of view of Jordanian governmental university according to some variables. The study sample was selected randomly from (365) male and female students of the University of Jordan and researcher used the descriptive analytical approach to suit the current study and adopted the questionnaire in order to collect information and achieve the goals of the study as the questionnaire items consisted of two domains. The first is family control and awareness and the second is the field of social skills development. The study reached several results, the most prominent of which is that the family plays a major role in reducing university violence, and the presence of statistically significant differences at the level of significance (α≤0.05) of the responses of the study sample depending on the difference in the gender variable and the work of the mother and the absence of statistically significant differences at the same significance attributed to variables of family size, scientific qualification of the mother, work of the father and scientific qualification of the father. The study recommended the need to educate families in reducing the manifestations and forms of violence in addition to attention to students and the university environment.